Pro-Calcitonin and C Reactive Protein as Marker of Infection: Evaluation of Systemic Inflammatory Response Syndrome (SIRS) in Patients with Normal and Impaired Renal Function - Nadeem Anjum , Muhammad Khurram , Madiha Sultan , Jianan Ren ,Guanwei Li, Nadeem Anjum , Muhammad Khurram , Madiha Sultan , Jianan Ren ,Guanwei Li (Journal of Rawalpindi Medical College, 2018)
Background: To investigate Pro-Calcitonin (PCT) and C reactive protein (CRP) as a predictor of infectious systemic inflammatory response syndrome (SIRS) in patients with normal and impaired renal function. Methods: In this cross-sectional study >18 year old patients with features suggestive of SIRS were included.PCT and CRP were done on the first day of admission. Based on clinical features and results of cultures, patients were divided into non-infection and infection (sepsis) groups. Based on glomerular filtration rate (GFR) patients were further divided to Group A (GFR ≥60ml/min) and Group B (GFR <60ml/min).Receiver operating characteristic (ROC) curve was used for statistical analysis. Results: Out of 740 patients, 48.3% were diagnosed to be suffering from infection (sepsis). GFR of 50.8% patients was ≥ 60 ml/min/1.73m2 (Group A), and GFR of 364 (49.2%) patients was < 60 ml/min/1.73m2(Group B).For prediction of infection in SIRS patients, ROC curve based AUC for PCT in all, Group A, and Group B patients was 0.84, 0.86, and 0.71 respectively. Similarly for CRP AUC was 0.81, 0.78, and 0.83 respectively. Best cut off value of PCT predicting the infectious cause of SIRS in all, Group A, and Group B patients was 0.24, 0.13, and0.93 ng/mL respectively. Similar best cut off value of PCT for all, Group A and B patients were 13.10 and 11.10 mg/L respectively. Conclusion: Initial PCT≥ 0.24ng/mL and CRP ≥ 13.10 mg/L are predictors of sepsis in SIRS patients. PCT is a better predictor for patients with normal and CRP better predictor for patients with deranged renal function.